TRANSFORMASI SENI TIGA DIMENSIONAL BALI - I Wayan Seriyoga Parta (Universitas Pendidikan Ganesha, 2010)
The art of carving in Bali has been considered as a part of the transformation fromthe soul’s sacrifice in the prehistoric period, which was continued untuil the arrivalof Hinduism-Buddhism influence, and also Chinese culture. Sculpture, at the beginning,served as a means of manifesting gods in Hinduism’s belief and is placedin temples. From this phenomenon, traditional statue come into existence, whichhave peculiar patterns or characteristics in terms of their figurations. This wasthen followed by the existence of traditional natural or autodidact artist in carving,who certainly had a good knowledge in the features of traditional carvings.However, in line with the development of the traditional carving art, the traditionalartists have been capable of development of the traditional carving art products,which are beyond the carving patterns that they have acquired. This results in anew form of creativity, which is appreciated as a modern carving art. The moderncarving art can be considered as an assimilation of local values and western interferencebrought by western artists to Bali. Even though there has been a stagnation,the Balinese carving has been developing in accordance with the dynamics ofthe time. From academic young artists, there appears a new development whichleads the art of carving to the development contemporary art, with its experimentalworks, not only in terms medium and material, but also in terms of creativityor thought in the form of installation art and multimedia. This fact has made theart of carving in Bali moves dynamically and experiences development untul now.Key words: carving art, Hinduism, traditional, religious, modern, contemporaryexperimental